Pengaruh Kualitas Layanan Terhadap Minat Beli Ulang Konsumen Nanostore (Studi Pada Konsumen Nanostore di Kota Bandung) - Maulinda, Mia; Harmon; Sayuti, Abdul Malik (Jurnal Riset Bisnis dan Investasi, 2023)
The retail industry in Indonesia is experiencing rapid progress as indicated by the expansion of modern retail in various regions. Nanostore is one form of traditional retail that is affected by the growth of modern retail. Nanostores number of rows according to the population in an area. The city of Bandung is experiencing an increase in population every year, indicating the large number of nanostores that compete with modern retail. The existence of modern retail has resulted in consumer expectations of high service quality. The purpose of the study was to determine the effect of service quality on consumer repurchase intention nanostores in Bandung. Data obtained as many as 414 respondents with purposive sampling technique. The research method uses descriptive quantitative and analytical techniques using descriptive analysis and simple regression analysis. The results of the study influence of service quality on consumers showed that the nanostore repurchase intention was 28%.